Documentation (Criminal justice institutions and the social trajectories of adolescents/youth in Burkina Faso: endogenous/local forms and patterns of punishment, 2021)
This communication covers presentation; mission and objectives; target audience; length of stay; placement method; administrative organization; care activities; monitoring-evaluation system; institution-child and young person-family relationship; sanctions applicable in boarding schools; some statistical data.
Keywords: Children; Education; Practical judgment; Social conflict; Juvenile detention; Juvenile delinquency; Vulnerability; Protection; Deprivation of Liberty; Preliminary Investigation; Investigation Phase; Enforcement of Decisions